PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI PADA KINERJA PENYUSUN LAPORAN KEUANGAN SATUAN KERJA MELALUI KOMITMEN ORGANISASI - Prakoso, Veryanto Adi; Ratnadi, Ni Made Dwi; Putri, IGAM Asri Dwija (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
This study aims to obtain empirical evidence of the influence of competence, organizational culture on performance of the financial report's authors work unit ministry/institutions through organizational commitment. The research was conducted at the working unit ministries / agencies in the area of ??payment KPPN Denpasar. Samples used as many as 144 respondents using purposive sampling technique. Data is collected using a questionnaire. Data were analyzed using Path Analysis. The results of this study indicate that competence of a positive effect on the performance of financial report's authors, organizational culture of positive effect on performance financial report's authors, organizational commitment of a positive effect on the performance of financial report's authors, competency of positive effect on organizational commitment of financial report's authors, organizational culture had no effect on organizational commitment of financial report's authors, competence of positive effect on the performance of the financial report's authors through organizational commitment and organizational culture of positive effect on the performance of the financial report's authors through organizational commitment.
Keywords: competence, organizational culture, organizational commitment, performance